CNT-Coated Quartz Woven Fabric Electrodes for Robust Lithium-ion Structural Batteries - Mi-Young Park; Chun-Gon Kim; Joo-Hyung Kim (Applied Sciences, 2020)
Reliability in various conditions for Li-ion batteries has been considered one of the most important factors when determining usability. Silica-based fabric has great potential to be an alternative material for electrode support, providing mechanical and physical stability in lithium-ion batteries. In this study, a carbon nanotube (CNT)-coated quartz woven fabric electrode (C-QWF) with impressive electrochemical characteristics was synthesized via a sequential two-step deposition process using Al and Fe as metal catalyst and CH4 as a carbon source. The C-QWF electrode exhibited a considerable specific discharge capacity of 369 mAh g−1 at a rate of 0.1 C-rate after cycling. The battery cell showed self-recovering ability during the cycling test at 1 C-rate, although the silica fabric has sluggish electrical conductivity. The C-QWF electrode has a superior electrochemical performance, providing new perspectives on textile fabric electrodes for robust Li-ion batteries, especially load-bearing structural batteries.